Climate change in the Middle East and North Africa - Thompson, William R., author.
1 online resource
Keywords: "Environmental factors in the Middle East and North Africa have played a crucial role in the historical and social development of the region. The book delves into a broad set of historical literature from the past 15,000 years that neglected to consider environmental factors to their full effect. Beyond the broad historic analysis, the chapters derive conclusions for today's debate on whether climate change leads to more social conflict and violence. Introducing a theoretical framework focused on adaptive cycling, this book probes and refines the role of climate in ancient and modern political-economic systems in the MENA region. It also underscores just how bad the 21st century environment may become thanks to global warming. While the MENA region may not survive the latest onslaught of deteriorating climate, there is also some interest in how a region that once led the world in introducing all sorts of innovations thousands of years ago has evolved into a contemporary setting characterized by traditional conservatism, poverty, and incessant strife. Emphasizing regional dynamics, the central question deals with the role of climate change in the rise and decline of the MENA region. The book will be a key resource to students and readers interested in global warming including academics and policy makers"--